A method for manufacturing a high-definition anti-fingerprint gun-gray mirror aluminum plate
By forming a multi-layer coating structure on the surface of the aluminum coil, the shortcomings of existing aluminum plates in fingerprint resistance and corrosion resistance are solved, and the manufacturing of high-definition anti-fingerprint gun gray mirror aluminum plates are realized, improving the overall performance and aesthetics of the product.
Patent Information
- Application Number
- CN202411805982.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The existing mirror aluminum plates have defects in their anti-fingerprint performance, and are prone to scratches, color aberration and other problems during the manufacturing process, which affects the overall quality of the product.
By forming a multi-layer coating structure on the surface of the aluminum coil, including anti-corrosion coating, mirror aluminum film and chromium metal film, and inorganic silicon film layer, the synergistic effect of these layers is used to improve the anti-fingerprint and corrosion resistance of the aluminum plate.
The high-definition anti-fingerprint gun gray mirror aluminum plate is achieved, which significantly improves the anti-fingerprint performance and aesthetics of the aluminum plate, while enhancing its corrosion resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal plates, and in particular to a method for manufacturing a high-definition anti-fingerprint gun-gray mirror aluminum plate. Background Art
[0002] With the rapid development of modern industry and technology, aluminum sheet materials have been widely used in many fields such as architectural decoration, electronic products, transportation, etc. due to their excellent properties such as light weight, corrosion resistance, and easy processing. However, traditional aluminum sheets often face problems such as fingerprint residue, easy surface scratches, and insufficient gloss during use, especially in high-demand visual environments, such as high-end electronic product housings and luxury car interiors. These problems are particularly prominent.
[0003] Although the mirror aluminum sheets on the current market meet the requirements of smoothness and glossiness to a certain extent, they still have obvious defects in anti-fingerprint performance. The residual fingerprints not only affect the appearance, but may also damage the coating on the surface of the aluminum sheet due to long-term contact, reducing its durability. In addition, during the manufacturing process of some mirror aluminum sheets, due to lax process control or improper material selection, scratches and color differences appear on the surface of the finished product, which seriously affects the overall quality of the product.
[0004] At present, most anti-fingerprint aluminum plates are coated with a single coating on their surface, and the best use effect in terms of anti-corrosion performance and anti-fingerprint performance has not yet been achieved. Therefore, developing a method that can synergistically improve the anti-corrosion performance and anti-fingerprint performance of aluminum plates through multiple coatings has become a technical problem that needs to be urgently solved by technical personnel in this field. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a method for manufacturing a high-definition anti-fingerprint gun-gray mirror aluminum plate, which can effectively solve the problem that the aluminum plate in the prior art has low definition and no anti-fingerprint function.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0007] A method for manufacturing a high-definition anti-fingerprint gun-gray mirror aluminum plate, the manufacturing method comprising the following steps:
[0008] S1. Add 6-8% of the weight of anti-corrosion filler to the UV coating, evenly disperse it, and apply it on the surface of the pre-treated aluminum coil using a fully automatic roller coating production line, and then cure it by ultraviolet irradiation. The obtained material is recorded as anti-corrosion aluminum material;
[0009] S2. Place the anti-corrosion aluminum material into the first layer of the vacuum coating machine. The electron gun uses a pure aluminum metal target. The electron gun emits a high-energy electron beam to bombard the aluminum target, forming a mirror aluminum film on the surface of the anti-corrosion aluminum material.
[0010] S3, placing the anti-corrosion aluminum material treated by S2 into the second layer of the vacuum coating machine, the electron gun uses a pure chromium metal target material, and the electron gun emits a high-energy electron beam to bombard the chromium target, forming a gun-gray chromium metal film layer on the outside of the mirror aluminum film of the anti-corrosion aluminum material;
[0011] S4. Place the anti-corrosion aluminum material treated by S3 into the third layer of the vacuum coating machine. The electron gun uses an inorganic silicon material target. The electron gun emits a high-energy electron beam to bombard the silicon target, forming an inorganic silicon film layer on the outside of the chromium metal film layer of the anti-corrosion aluminum material. The result is a high-definition anti-fingerprint gun gray mirror aluminum plate.
[0012] Furthermore, in S1, the steps of preparing the anticorrosive filler are:
[0013] Step 2.1, weigh 4 g of mica iron oxide and disperse it in 70 mL of anhydrous ethanol, disperse it ultrasonically at a frequency of 28 kHz for 30 min, then add ammonia water to adjust the pH value to 8, and the result is recorded as the iron oxide component;
[0014] Step 2.2, weigh 5g of ethyl orthosilicate and disperse it in 80mL of anhydrous ethanol. Stir it at a stirring speed of 500r / min for 30min, then pour in the iron oxide component and stir it at a stirring speed of 300r / min for 6h in a water bath at 80°C. After centrifugation to remove the supernatant, rinse it with acetone three times to obtain the anti-corrosion filler.
[0015] The preparation steps of the UV coating are:
[0016] Step 1, weigh 120g 1,3-propylene glycol, 50g ethylene glycol, 38g sodium 5-sulfoisophthalate and 0.4g sodium hydroxide into a flask, heat to 120°C and keep warm for 3h, then heat to 190°C again and keep warm for 1h, finally cool to 120°C and add 13g di(trimethylol)propane, 20g phthalic anhydride, 100g dodecane dibasic acid, 180g maleic acid and 0.2g p-hydroxyanisole, heat to 200°C and keep warm for 2h, then cool to 130°C, add 45g glycidyl methacrylate dropwise and continue to keep warm for 2h, the result is recorded as a water-based unsaturated polyester component;
[0017] Step 2, cooling the aqueous unsaturated polyester component to 100° C. and adding deionized water to adjust the solid content to 70%, and the resultant is recorded as the aqueous dispersion component;
[0018] Step 3, weigh 12g of aqueous dispersion component, 7g of propylene glycol methyl ether acetate, 7g of isopropanol, 0.2g of polyoxyethylene alkyl alcohol amide and 20g of deionized water into a flask, stir at a stirring speed of 600r / min for 20min, then add 25g of photoinitiator TPO, and continue stirring at the original stirring speed for 10min. The result is recorded as the photoinitiator component;
[0019] Step 4: weigh 55 g of aqueous dispersion component, 5 g of photoinitiator component, 4 g of propylene glycol methyl ether acetate, 3 g of isopropyl alcohol, 15 g of deionized water and 0.2 g of silicone leveling agent, mix them, and stir at a stirring speed of 2500 r / min for 30 min to obtain a UV coating.
[0020] Furthermore, in S1, the specific steps of pre-processing are:
[0021] Step 3.1, soak the aluminum coil in a 5% sodium hydroxide aqueous solution, soak for 20 seconds, rinse with deionized water three times, and dry at 55°C for 5-6 hours;
[0022] Step 3.2, soak the aluminum coil treated in step 3.1 in a 10% hydrochloric acid solution, control the temperature of the hydrochloric acid solution to 60-65°C and soak for 15 seconds, then rinse with deionized water 3 times and dry at 55°C for 5-6 hours.
[0023] Furthermore, in S1, the specific operation of ultraviolet irradiation is 800-1000mj / cm 2 Irradiate with UV energy for 3-5 minutes.
[0024] Furthermore, in S2, the conveying speed of the aluminum target is 0.2-0.6 m / min, and the thickness of the mirror aluminum film is 80-100 nm.
[0025] Furthermore, in S3, the conveying speed of the chromium target is 0.1-0.3 m / min, and the thickness of the mirror aluminum film is 40-80 nm.
[0026] Furthermore, in S4, the preparation steps of the inorganic silicon material target are:
[0027] Step 6.1, mixing silicon carbide powder, carbon powder and silicon powder in a weight ratio of 1:3:4, pouring the mixed powder into a ball mill for ball milling, and the obtained powder is recorded as mixed powder;
[0028] Step 6.2: After the mixed powder is molded, it is placed in a hot pressing furnace and kept at a temperature of 1380-1400°C for 1 hour, then the temperature is raised to 1980°C and kept for 2 hours, and hot pressing is performed at a pressure of 70 MPa to obtain an inorganic silicon material target.
[0029] Furthermore, in step 6.1, the ball milling speed is 1000 r / min, and the ball milling time is 24 h.
[0030] Furthermore, in S4, the conveying speed of the silicon target is 0.1-0.3 m / min, and the thickness of the mirror aluminum film is 20-40 nm.
[0031] The present invention provides a method for manufacturing a high-definition anti-fingerprint gun-gray mirror aluminum plate. Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The present invention first pre-treats the aluminum coil, and soaks it in a sodium hydroxide solution to remove oil impurities on the surface of the aluminum coil, and soaks it in a hydrochloric acid solution to remove rust such as aluminum oxide on the surface of the aluminum coil, thereby facilitating post-coating treatment.
[0033] 2. The present invention coats the surface of mica iron oxide with nano-silicon dioxide and then adds it to the UV coating, and then forms an anti-corrosion coating on the surface of the aluminum coil by coating, which can significantly improve the corrosion resistance of the coating, improve the physical properties of the coating, optimize the microstructure of the coating, and enhance the comprehensive performance of the coating; the flaky structure of mica iron oxide itself can prevent the diffusion and transmission of corrosive media, and by coating the surface with nano-silicon dioxide, this barrier effect is further enhanced. The small size effect and high specific surface area of nano-silicon dioxide make the coating denser, reduce the channels for the penetration of corrosive media, and thus improve the corrosion resistance of the coating.
[0034] 3. The present invention uses silicon carbide powder, carbon powder and silicon powder as raw materials to prepare inorganic silicon material targets by hot pressing, which can form an inorganic silicon thin film layer with anti-corrosion and anti-fingerprint effects on the surface of the aluminum plate. The inorganic silicon material target prepared by mixing silicon carbide powder, carbon powder and silicon powder can increase the density of the inorganic silicon thin film layer, thereby improving the corrosion resistance and anti-fingerprint performance of the aluminum plate; secondly, by adding a chromium metal film layer and a mirror aluminum film, the prepared aluminum plate can have a gun gray mirror effect, thereby improving the aesthetics of the aluminum plate. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The present invention will be further described below in conjunction with the embodiments.
[0037] Example 1
[0038] The present embodiment provides a method for manufacturing a high-definition anti-fingerprint gunmetal gray mirror aluminum plate, the manufacturing method comprising the following steps:
[0039] S1. Add 6% of the weight of anticorrosive filler to the UV coating, disperse it evenly and apply it on the surface of the pre-treated aluminum coil using a fully automatic roller coating production line. Then, 2 The material was cured by irradiating it with UV energy for 3 minutes, and the obtained material was recorded as anti-corrosion aluminum material.
[0040] Wherein, the preparation steps of the anticorrosive filler are:
[0041] Step 2.1, weigh 4 g of mica iron oxide and disperse it in 70 mL of anhydrous ethanol, disperse it ultrasonically at a frequency of 28 kHz for 30 min, then add ammonia water to adjust the pH value to 8, and the result is recorded as the iron oxide component;
[0042] Step 2.2, weigh 5g of ethyl orthosilicate and disperse it in 80mL of anhydrous ethanol. Stir it at a stirring speed of 500r / min for 30min, then pour in the iron oxide component and stir it at a stirring speed of 300r / min for 6h in a water bath at 80°C. After centrifugation to remove the supernatant, rinse it with acetone three times to obtain the anti-corrosion filler.
[0043] The preparation steps of UV coating are:
[0044] Step 1, weigh 120g 1,3-propylene glycol, 50g ethylene glycol, 38g sodium 5-sulfoisophthalate and 0.4g sodium hydroxide into a flask, heat to 120°C and keep warm for 3h, then heat to 190°C again and keep warm for 1h, finally cool to 120°C and add 13g di(trimethylol)propane, 20g phthalic anhydride, 100g dodecane dibasic acid, 180g maleic acid and 0.2g p-hydroxyanisole, heat to 200°C and keep warm for 2h, then cool to 130°C, add 45g glycidyl methacrylate dropwise and continue to keep warm for 2h, the result is recorded as a water-based unsaturated polyester component;
[0045] Step 2, cooling the aqueous unsaturated polyester component to 100° C. and adding deionized water to adjust the solid content to 70%, and the resultant is recorded as the aqueous dispersion component;
[0046] Step 3, weigh 12g of aqueous dispersion component, 7g of propylene glycol methyl ether acetate, 7g of isopropanol, 0.2g of polyoxyethylene alkyl alcohol amide and 20g of deionized water into a flask, stir at a stirring speed of 600r / min for 20min, then add 25g of photoinitiator TPO, and continue stirring at the original stirring speed for 10min. The result is recorded as the photoinitiator component;
[0047] Step 4: weigh 55 g of aqueous dispersion component, 5 g of photoinitiator component, 4 g of propylene glycol methyl ether acetate, 3 g of isopropyl alcohol, 15 g of deionized water and 0.2 g of silicone leveling agent, mix them, and stir at a stirring speed of 2500 r / min for 30 min to obtain a UV coating.
[0048] The specific steps of pre-processing are:
[0049] Step 3.1, soak the aluminum coil in a 5% sodium hydroxide aqueous solution, soak for 20 seconds, rinse with deionized water three times, and dry at 55°C for 5 hours;
[0050] Step 3.2, soak the aluminum coil treated in step 3.1 in a 10% hydrochloric acid solution, control the temperature of the hydrochloric acid solution to 60°C and soak for 15 seconds, then rinse with deionized water 3 times and dry at 55°C for 5 hours.
[0051] S2. Place the anti-corrosion aluminum material into the first layer of the vacuum coating machine. The electron gun uses pure aluminum metal target material. The electron gun emits a high-energy electron beam to bombard the aluminum target, forming a mirror aluminum film on the surface of the anti-corrosion aluminum material. The conveying speed of the aluminum target is 0.2m / min, and the thickness of the mirror aluminum film is 80nm.
[0052] S3. Place the anti-corrosion aluminum material treated by S2 into the second layer of the vacuum coating machine. The electron gun uses pure chromium metal target material. The electron gun emits a high-energy electron beam to bombard the chromium target, forming a gun-gray chromium metal film layer on the outside of the mirror aluminum film of the anti-corrosion aluminum material. The conveying speed of the chromium target is 0.1m / min, and the thickness of the mirror aluminum film is 40nm.
[0053] S4. Place the anti-corrosion aluminum material treated by S3 into the third layer of the vacuum coating machine. The electron gun uses an inorganic silicon material target. The electron gun emits a high-energy electron beam to bombard the silicon target, forming an inorganic silicon film layer on the outside of the chromium metal film layer of the anti-corrosion aluminum material. The result is a high-definition anti-fingerprint gun gray mirror aluminum plate. The conveying speed of the silicon target is 0.1m / min, and the thickness of the mirror aluminum film is 20nm.
[0054] Among them, the preparation steps of inorganic silicon material target are:
[0055] Step 6.1, silicon carbide powder, carbon powder and silicon powder are mixed in a weight ratio of 1:3:4, poured into a ball mill and milled at a speed of 1000 r / min for 24 hours, and the obtained powder is recorded as mixed powder;
[0056] Step 6.2: After the mixed powder is molded, it is placed in a hot pressing furnace and kept at 1380°C for 1 hour. Then, the temperature is raised to 1980°C and kept for 2 hours. Hot pressing is performed at a pressure of 70 MPa to obtain an inorganic silicon material target.
[0057] Example 2
[0058] The present embodiment provides a method for manufacturing a high-definition anti-fingerprint gunmetal gray mirror aluminum plate, the manufacturing method comprising the following steps:
[0059] S1. Add 8% of the weight of anticorrosive filler to the UV coating, disperse it evenly and apply it on the surface of the pre-treated aluminum coil using a fully automatic roller coating production line. Then, 2 The material was irradiated with UV energy for 5 minutes for curing, and the obtained material was recorded as anti-corrosion aluminum material.
[0060] Wherein, the preparation steps of the anticorrosive filler are:
[0061] Step 2.1, weigh 4 g of mica iron oxide and disperse it in 70 mL of anhydrous ethanol, disperse it ultrasonically at a frequency of 28 kHz for 30 min, then add ammonia water dropwise to adjust the pH value to 8, and the result is recorded as the iron oxide component;
[0062] Step 2.2, weigh 5g of ethyl orthosilicate and disperse it in 80mL of anhydrous ethanol. Stir it at a stirring speed of 500r / min for 30min, then pour in the iron oxide component and stir it at a stirring speed of 300r / min for 6h in a water bath at 80°C. After centrifugation to remove the supernatant, rinse it with acetone three times to obtain the anti-corrosion filler.
[0063] The preparation steps of UV coating are:
[0064] Step 1, weigh 120g 1,3-propylene glycol, 50g ethylene glycol, 38g sodium 5-sulfoisophthalate and 0.4g sodium hydroxide into a flask, heat to 120°C and keep warm for 3h, then heat to 190°C again and keep warm for 1h, finally cool to 120°C and add 13g di(trimethylol)propane, 20g phthalic anhydride, 100g dodecane dibasic acid, 180g maleic acid and 0.2g p-hydroxyanisole, heat to 200°C and keep warm for 2h, then cool to 130°C, add 45g glycidyl methacrylate dropwise and continue to keep warm for 2h, the result is recorded as a water-based unsaturated polyester component;
[0065] Step 2, cooling the aqueous unsaturated polyester component to 100° C. and adding deionized water to adjust the solid content to 70%, and the resultant is recorded as the aqueous dispersion component;
[0066] Step 3, weigh 12g of aqueous dispersion component, 7g of propylene glycol methyl ether acetate, 7g of isopropanol, 0.2g of polyoxyethylene alkyl alcohol amide and 20g of deionized water into a flask, stir at a stirring speed of 600r / min for 20min, then add 25g of photoinitiator TPO, and continue stirring at the original stirring speed for 10min. The result is recorded as the photoinitiator component;
[0067] Step 4: weigh 55 g of aqueous dispersion component, 5 g of photoinitiator component, 4 g of propylene glycol methyl ether acetate, 3 g of isopropyl alcohol, 15 g of deionized water and 0.2 g of silicone leveling agent, mix them, and stir at a stirring speed of 2500 r / min for 30 min to obtain a UV coating.
[0068] The specific steps of pre-processing are:
[0069] Step 3.1, immerse the aluminum coil in a 5% sodium hydroxide aqueous solution, soak for 20 seconds, rinse with deionized water three times, and dry at 55°C for 6 hours;
[0070] Step 3.2, immerse the aluminum coil treated in step 3.1 in a 10% hydrochloric acid solution, control the temperature of the hydrochloric acid solution to 65°C and immerse for 15 seconds, then rinse with deionized water 3 times and dry at 55°C for 6 hours.
[0071] S2. Place the anti-corrosion aluminum material into the first layer of the vacuum coating machine. The electron gun uses pure aluminum metal target material. The electron gun emits a high-energy electron beam to bombard the aluminum target, forming a mirror aluminum film on the surface of the anti-corrosion aluminum material. The conveying speed of the aluminum target is 0.6m / min, and the thickness of the mirror aluminum film is 100nm.
[0072] S3. Place the anti-corrosion aluminum material treated by S2 into the second layer of the vacuum coating machine. The electron gun uses pure chromium metal target material. The electron gun emits a high-energy electron beam to bombard the chromium target, forming a gun-gray chromium metal film layer on the outside of the mirror aluminum film of the anti-corrosion aluminum material. The conveying speed of the chromium target is 0.3m / min, and the thickness of the mirror aluminum film is 80nm.
[0073] S4. Place the anti-corrosion aluminum material treated by S3 into the third layer of the vacuum coating machine. The electron gun uses an inorganic silicon material target. The electron gun emits a high-energy electron beam to bombard the silicon target, forming an inorganic silicon film layer on the outside of the chromium metal film layer of the anti-corrosion aluminum material. The result is a high-definition anti-fingerprint gun gray mirror aluminum plate. The conveying speed of the silicon target is 0.3m / min, and the thickness of the mirror aluminum film is 40nm.
[0074] Among them, the preparation steps of inorganic silicon material target are:
[0075] Step 6.1, silicon carbide powder, carbon powder and silicon powder are mixed in a weight ratio of 1:3:4, poured into a ball mill and milled at a speed of 1000 r / min for 24 hours, and the obtained powder is recorded as mixed powder;
[0076] Step 6.2: After the mixed powder is molded, it is placed in a hot pressing furnace and kept at 1400°C for 1 hour. Then, the temperature is raised to 1980°C and kept at this temperature for 2 hours. Hot pressing is performed at a pressure of 70 MPa to obtain an inorganic silicon material target.
[0077] Example 3
[0078] The present embodiment provides a method for manufacturing a high-definition anti-fingerprint gunmetal gray mirror aluminum plate, the manufacturing method comprising the following steps:
[0079] S1. Add 7% of the weight of anticorrosive filler to the UV coating, disperse it evenly and apply it on the pre-treated aluminum coil surface using a fully automatic roller coating production line. Then, 2 The material is irradiated with UV energy for 3-5 minutes for curing, and the obtained material is recorded as anti-corrosion aluminum material.
[0080] Wherein, the preparation steps of the anticorrosive filler are:
[0081] Step 2.1, weigh 4 g of mica iron oxide and disperse it in 70 mL of anhydrous ethanol, disperse it ultrasonically at a frequency of 28 kHz for 30 min, then add ammonia water dropwise to adjust the pH value to 8, and the result is recorded as the iron oxide component;
[0082] Step 2.2, weigh 5g of ethyl orthosilicate and disperse it in 80mL of anhydrous ethanol. Stir it at a stirring speed of 500r / min for 30min, then pour in the iron oxide component and stir it at a stirring speed of 300r / min for 6h in a water bath at 80°C. After centrifugation to remove the supernatant, rinse it with acetone three times to obtain the anti-corrosion filler.
[0083] The preparation steps of UV coating are:
[0084] Step 1, weigh 120g 1,3-propylene glycol, 50g ethylene glycol, 38g sodium 5-sulfoisophthalate and 0.4g sodium hydroxide into a flask, heat to 120°C and keep warm for 3h, then heat to 190°C again and keep warm for 1h, finally cool to 120°C and add 13g di(trimethylol)propane, 20g phthalic anhydride, 100g dodecane dibasic acid, 180g maleic acid and 0.2g p-hydroxyanisole, heat to 200°C and keep warm for 2h, then cool to 130°C, add 45g glycidyl methacrylate dropwise and continue to keep warm for 2h, the result is recorded as a water-based unsaturated polyester component;
[0085] Step 2, cooling the aqueous unsaturated polyester component to 100° C. and adding deionized water to adjust the solid content to 70%, and the resultant is recorded as the aqueous dispersion component;
[0086] Step 3, weigh 12g of aqueous dispersion component, 7g of propylene glycol methyl ether acetate, 7g of isopropanol, 0.2g of polyoxyethylene alkyl alcohol amide and 20g of deionized water into a flask, stir at a stirring speed of 600r / min for 20min, then add 25g of photoinitiator TPO, and continue stirring at the original stirring speed for 10min. The result is recorded as the photoinitiator component;
[0087] Step 4: weigh 55 g of aqueous dispersion component, 5 g of photoinitiator component, 4 g of propylene glycol methyl ether acetate, 3 g of isopropyl alcohol, 15 g of deionized water and 0.2 g of silicone leveling agent, mix them, and stir at a stirring speed of 2500 r / min for 30 min to obtain a UV coating.
[0088] The specific steps of pre-processing are:
[0089] Step 3.1, immerse the aluminum coil in a 5% sodium hydroxide aqueous solution, soak for 20 seconds, rinse with deionized water three times, and dry at 55°C for 6 hours;
[0090] Step 3.2, soak the aluminum coil treated in step 3.1 in a 10% hydrochloric acid solution, control the temperature of the hydrochloric acid solution to 63°C and soak for 15 seconds, then rinse with deionized water for 3 times and dry at 55°C for 6 hours.
[0091] S2. Place the anti-corrosion aluminum material into the first layer of the vacuum coating machine. The electron gun uses pure aluminum metal target material. The electron gun emits a high-energy electron beam to bombard the aluminum target, forming a mirror aluminum film on the surface of the anti-corrosion aluminum material. The conveying speed of the aluminum target is 0.4m / min, and the thickness of the mirror aluminum film is 90nm.
[0092] S3. Place the anti-corrosion aluminum material treated by S2 into the second layer of the vacuum coating machine. The electron gun uses pure chromium metal target material. The electron gun emits a high-energy electron beam to bombard the chromium target, forming a gun-gray chromium metal film layer on the outside of the mirror aluminum film of the anti-corrosion aluminum material. The conveying speed of the chromium target is 0.2m / min, and the thickness of the mirror aluminum film is 60nm.
[0093] S4. Place the anti-corrosion aluminum material treated by S3 into the third layer of the vacuum coating machine. The electron gun uses an inorganic silicon material target. The electron gun emits a high-energy electron beam to bombard the silicon target, forming an inorganic silicon film layer on the outside of the chromium metal film layer of the anti-corrosion aluminum material. The result is a high-definition anti-fingerprint gun gray mirror aluminum plate. The conveying speed of the silicon target is 0.2m / min, and the thickness of the mirror aluminum film is 30nm.
[0094] Among them, the preparation steps of inorganic silicon material target are:
[0095] Step 6.1, silicon carbide powder, carbon powder and silicon powder are mixed in a weight ratio of 1:3:4, poured into a ball mill and milled at a speed of 1000 r / min for 24 hours, and the obtained powder is recorded as mixed powder;
[0096] Step 6.2: After the mixed powder is molded, it is placed in a hot pressing furnace and kept at 1390°C for 1 hour. Then, the temperature is raised to 1980°C and kept for 2 hours. Hot pressing is performed under a pressure of 70 MPa to obtain an inorganic silicon material target.
[0097] Comparative Example 1
[0098] The manufacturing method of a high-definition anti-fingerprint gun-gray mirror aluminum plate provided in this comparative example is substantially the same as that in Example 1, the main difference is that in this comparative example 1, the anti-corrosion filler in Example 1 is replaced by nano-silicon dioxide.
[0099] Comparative Example 2
[0100] The manufacturing method of a high-definition anti-fingerprint gun-gray mirror aluminum plate provided in this comparative example is substantially the same as that in Example 1, the main difference is that in this comparative example 2, the inorganic silicon material target in Example 1 is replaced with silicon carbide powder.
[0101] Performance Testing
[0102] The high-definition anti-fingerprint gunmetal gray mirror aluminum plates in Examples 1-3 and Comparative Examples 1-2 are marked as Example 1, Example 2, Example 3, Comparative Example 1, and Comparative Example 2, respectively. Then, the performance of Examples 1-3 and Comparative Examples 1-2 is tested. The specific testing method is as follows:
[0103] 1. Clarity detection: observe the smoothness, color uniformity and presence of scratches of the high-definition anti-fingerprint gun-gray mirror aluminum plates in Examples 1-3 and Comparative Examples 1-2. Good smoothness, uniform color and absence of scratches are recorded as qualified, otherwise they are recorded as unqualified. The obtained data are recorded in the following table.
[0104] 2. Anti-fingerprint performance test: Touch the high-definition anti-fingerprint gun-gray mirror aluminum plates in Examples 1-3 and Comparative Examples 1-2 with your fingers to see if fingerprints are left. If no fingerprints are left, it is considered qualified, otherwise it is considered unqualified. The obtained data are recorded in the following table.
[0105]
[0106] It can be seen from the data in the above table that the high-definition anti-fingerprint gun gray mirror aluminum plates prepared in Examples 1-3 have good clarity and anti-fingerprint performance, while Comparative Example 1 has insufficient clarity compared to the high-definition anti-fingerprint gun gray mirror aluminum plates prepared in Examples 1-3, and Comparative Example 2 has poor anti-fingerprint performance compared to the high-definition anti-fingerprint gun gray mirror aluminum plates prepared in Examples 1-3, indicating that the anti-corrosion filler and inorganic silicon material target added in the process of preparing the high-definition anti-fingerprint gun gray mirror aluminum plate can improve the clarity and anti-fingerprint performance of the aluminum plate.
[0107] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0108] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for manufacturing a high-definition anti-fingerprint gun-gray mirror aluminum plate, characterized in that: The manufacturing method comprises the following steps: S1. Add 6-8% of the weight of anti-corrosion filler to the UV coating, evenly disperse it, and apply it on the surface of the pre-treated aluminum coil using a fully automatic roller coating production line, and then cure it by ultraviolet irradiation. The result is recorded as anti-corrosion aluminum material; S2. Place the anti-corrosion aluminum material into the first layer of the vacuum coating machine. The electron gun uses a pure aluminum metal target. The electron gun emits a high-energy electron beam to bombard the aluminum target, forming a mirror aluminum film on the surface of the anti-corrosion aluminum material. S3, placing the anti-corrosion aluminum material treated by S2 into the second layer of the vacuum coating machine, the electron gun uses a pure chromium metal target material, and the electron gun emits a high-energy electron beam to bombard the chromium target, forming a gun-gray chromium metal film layer on the outside of the mirror aluminum film of the anti-corrosion aluminum material; S4, placing the anti-corrosion aluminum material treated by S3 into the third layer of the vacuum coating machine, the electron gun uses an inorganic silicon material target, the electron gun emits a high-energy electron beam to bombard the silicon target, and an inorganic silicon thin film layer is formed on the outside of the chromium metal film layer of the anti-corrosion aluminum material, and the result is a high-definition anti-fingerprint gun gray mirror aluminum plate; The preparation steps of the anticorrosive filler are: Step 2.1, weigh 4 g of mica iron oxide and disperse it in 70 mL of anhydrous ethanol, disperse it ultrasonically at a frequency of 28 kHz for 30 min, then add ammonia water dropwise to adjust the pH value to 8, and the result is recorded as the iron oxide component; Step 2.2, weigh 5 g of ethyl orthosilicate and disperse it in 80 mL of anhydrous ethanol, stir it at a stirring speed of 500 r / min for 30 min, then pour in the iron oxide component and stir it at a stirring speed of 300 r / min for 6 h in a water bath at 80°C, centrifuge to remove the supernatant, and rinse it with acetone three times to obtain the anticorrosive filler; The preparation steps of inorganic silicon material target are as follows: Step 6.1, mixing silicon carbide powder, carbon powder and silicon powder in a weight ratio of 1:3:4, pouring the mixed powder into a ball mill for ball milling, and the obtained powder is recorded as mixed powder; Step 6.2: After the mixed powder is molded, it is placed in a hot pressing furnace and kept at a temperature of 1380-1400°C for 1 hour, then the temperature is raised to 1980°C and kept for 2 hours, and hot pressing is performed at a pressure of 70 MPa to obtain an inorganic silicon material target.
2. The method for manufacturing a high-definition anti-fingerprint gunmetal gray mirror aluminum plate according to claim 1, characterized in that: In S1, the specific steps of pre-processing are: Step 3.1, soak the aluminum coil in a 5% sodium hydroxide aqueous solution, soak for 20 seconds, rinse with deionized water three times, and dry at 55°C for 5-6 hours; Step 3.2, soak the aluminum coil treated in step 3.1 in a 10% hydrochloric acid solution, control the temperature of the hydrochloric acid solution to 60-65°C and soak for 15 seconds, then rinse with deionized water 3 times and dry at 55°C for 5-6 hours.
3. The method for manufacturing a high-definition anti-fingerprint gunmetal gray mirror aluminum plate according to claim 1, characterized in that: In S1, the specific operation of UV irradiation is 800-1000mj / cm 2 Irradiate with UV energy for 3-5min.
4. The method for manufacturing a high-definition anti-fingerprint gunmetal gray mirror aluminum plate according to claim 1, characterized in that: In S2, the conveying speed of the aluminum target is 0.2-0.6 m / min, and the thickness of the mirror aluminum film is 80-100 nm.
5. The method for manufacturing a high-definition anti-fingerprint gunmetal gray mirror aluminum plate according to claim 1, characterized in that: In S3, the conveying speed of the chromium target is 0.1-0.3 m / min, and the thickness of the mirror aluminum film is 40-80 nm.
6. The method for manufacturing a high-definition anti-fingerprint gunmetal gray mirror aluminum plate according to claim 5, characterized in that: In step 6.1, the ball milling speed is 1000 r / min and the ball milling time is 24 h.
7. The method for manufacturing a high-definition anti-fingerprint gunmetal gray mirror aluminum plate according to claim 1, characterized in that: In S4, the conveying speed of the silicon target is 0.1-0.3 m / min, and the thickness of the mirror aluminum film is 20-40 nm.
Citation Information
Patent Citations
High-performance surface structure of electroplated mirror surface
CN113118000A
Electronic equipment shell, and manufacturing method thereof and electronic equipment
CN113316333A